Recent Referees (Journal of Political Economy, 2020)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Ran AbramitzkyJerome AddaAchyuta AdhvaryuHassan AfrouziFrancesco AgostinelliMarina AgranovLuis AguiarGabriel AhlfeldtAnders AkermanFrancesco AmodioOla AnderssonIsaiah AndrewsJose ApesteguiaPeter ArcidiaconoCarolina ArteagaDavid AtkinChristopher AveryScott BakerTetyana BalyukMarco BassettoJess BenhabibAllen BergerTheodore BergstromMichael BestSourav BhattacharyaManudeep BhullerSaki BigioMark BilsJaroslav BorovičkaJonathan BrogaardAline ButikoferIvan CanayDavide CantoniAlexander CappelenHector ChadeKam ChanLaurens CherchyeJudith ChevalierGabe Chodorow-ReichJeffrey ClemensAllan Collard-WexlerCody CookSimon CowanJanet CurrieEszter CziborGordon DahlMelissa DellManasi DeshpandeFrancesc DilmeDavid DornJoseph DoyleAnna Dreber AlmenbergMehmet EkmekciGlenn EllisonBenjamin EnkeLarry EpsteinHanming FangHenry FarberErnst FehrShuaizhang FengJon H. FivaOlle FolkeAndrew FosterEric FrenchChao FuYana GallenPeter GanongJorge Luis GarciaAlvaro Garcia MarinChristopher GarmonPieter GautierXavier GiroudBart GolsteynFrancois GourioTal GrossRaymond GuiterasKareem HaggagBen HandelBenjamin HansenNikolaj HarmonDavid HémousJonas HjortScott HolladayCosmin IlutNir JaimovichPamela JakielaGregor JaroschDavid Jimenez-GomezCharles JonesBoyan JovanovicBruno JullienAdam KaporKristian Bernt KarlsonMaximilian KasyAyumu KikkawaPhilipp KircherAndras KissPatrick KlineAsen KochovRalph KoijenAnton KolotilinAnton KorinekAndreas KotsadamAmanda KowalskiArvind KrishnamurthyZoe KuehnMoritz KuhnPablo KurlatNicola LaceteraRasmus LandersoeKevin LangFabian LangeJacob LaRiviereMichael LeeDavid LeeJosh LernerJustin LeungEdwin LeuvenSteven LevittShengwu LiIlse LindenlaubXiaodong LiuAlessandro LizzeriLee LockwoodKatrine LokenJingfeng LuJay LuMargaux LufladeErzo LuttmerGiovanni MastrobuoniMaurizio MazzoccoAtif MianKevin MilliganJosepa (Pepita) Miquel-FlorensaAhmed MobarakSidharth MoktanBenny MoldovanuCorina MommaertsMelanie MortenChristian MoserPetra MoserJack MountjoyRebecca MyersonJesse NaidooDavid NeumarkYew-Kwang NgAntonella NoccoScott OrrMatthew OsborneAdam OsmanAmanda PallaisJessica PanCecilia ParlatoreNicola PavaniniHarry PeiPaolo Giovanni PiacquadioJustin PierceRodrigo PintoRoland RathelotImke ReimersPascual RestrepoJames RobertsGuillaume RocheteauRichard RosenMark RosenzweigEsteban Rossi-HansbergMaya Rossin-SlaterJohn RustFelipe SaffieHeather SarsonsKlaus SchmidtMatthew SerflingCarl ShapiroAjay ShenoyHenrik SigstadChristopher SimsAndrzej SkrzypaczDag Einar SommervollIsaac SorkinMichelle SovinskyCharles SprengerStefanie StantchevaMeredith StartzMelvin StephensDavid StrombergAshley SwansonHuan TangDmitry TaubinskyVeikko ThieleDanna ThomasPeter ThompsonPetra ToddMirco ToninAlexander TorgovitskyFabrice TourreChristopher UdryArthur van BenthemStijn Van NieuwerburghJohn Van ReenenDimitri VayanosJulian Vedeler JohnsenFrederic VermeulenRajiv VohraNico VoigtlaenderMatthew WeinbergMarek WeretkaBen WilliamsChristian WolfAsher WolinskyArlene WongRandall WrightYanhui WuErte XiaoYuichi YamamotoMotohiro YogoNoam YuchtmanGiulia ZacchiaBasit ZafarSeth ZimmermanUlf Zoelitz Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 128, Number 2February 2020 Article DOIhttps://doi.org/10.1086/708481 © 2020 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.